Interventions that support major life transitions in older adulthood: a systematic review. (11th July 2018) - Vrkljan, Brenda; Montpetit, Ariane; Naglie, Gary; Rapoport, Mark; Mazer, Barbara
ABSTRACT: Background: Major life transitions can negatively impact the emotional well-being of older people. This study examined the effectiveness of interventions that target the three most common transitions in later life, namely bereavement, retirement, and relocation. Methods: A systematic search was performed via MEDLINE, EMBASE, CINAHL, Cochrane Library, PsycINFO, and reference lists of retrieved non-randomized and randomized controlled trials (RCTs) in English that studied the effectiveness of interventions addressing the three transitions in those >50 years of age. Two researchers independently selected the publications, piloted the data extraction form, and critically appraised studies specific to transition type and study design. Results: A total of 11 studies (bereavement: 7; retirement: 2; relocation: 2) of 8 unique interventions met the inclusion criteria of which nine were RCTs and two were of quasi-experimental designs were reviewed. Six studies were group-based interventions, three studies used individualized sessions, and one intervention used a combination of group and individualized programming. Group size varied (20–32 participants), as did qualifications of those administering the interventions. The methodological quality of included studies was weak. Findings suggest that group-based approaches provided by trained personnel can mitigate the negative health-related consequences associated with major transitions in later life. Conclusion: Evidence concerning interventions that address mental health challenges associated with these major transitions is limited. Future research should better characterize participants at study outset and use validated measures to capture effectiveness. Use of peer mentorship to navigate such transitions is promising, but given the small number of studies and their methodological weaknesses, further research on effectiveness is warranted.